Postgraduate Training Needs Among Pedagogical Students at Hanoi Metropolitan University: Current Situation and Solutions - Cuong Hong Do (Vietnam Journal of Education, 2023)
In the contemporary job market, individuals face demanding requirements that necessitate acquiring skills and deepening specialized knowledge. This is particularly evident in the education sector, where teachers are expected to possess advanced qualifications. Therefore, it becomes crucial to understand the current aspirations and needs of pedagogical students regarding postgraduate training. This research aims to examine the optimal timing and approaches for pursuing higher education and explore the specialization areas that are believed to effectively meet the job demands in mainstream schools. By addressing these pivotal research inquiries, this study aims to provide valuable insights for the development of postgraduate training programs tailored to the specific needs of pedagogical students and the demands of the education sector. Based on a survey of 283 final-year pedagogical students at Hanoi Metropolitan University and utilizing the SPSS 16 software for analysis, the research team has identified the causes of postgraduate aspirations, the level of demand, and the desired areas of specialization for postgraduate training. Additionally, they have evaluated the factors influencing the learning needs of the target group, which comprises final-year pedagogical students. The research results on the current situation serve as a foundation for investigating strategies to improve the quality of postgraduate education, provide guidance for postgraduate recruitment, and suggest the introduction of new educational programs in the field of education at Hanoi Metropolitan University, as well as other teacher training institutions.